Costumbres que tenemos en comn - Haro Sandoval, Esvilda Yane (2019)
The present work of professional sufficiency titled: What customs do we have in common?, has the purpose of sustain and argue the application through a lesson learning to the students of third grade of the secondary level at Luis Felipe de la Puente Uceda school, that they know and revalue the customs and traditions of our Julcn town in a framework to the competence of the convivence and democratic participation in search of common good and the performance of exchanging cultural practices in relation to life styles showing respect for the differences and that we only put it in evidence in this lesson learning to educate to the students in a significate way. _x000D_ To this end, have been employed a great diversity of learning strategies as the motivation, previous knowledge, cognitive conflict, among others. Which they be able to wake up the interest in the students with the purpose that can be taken advantage of by them. _x000D_ The present work consists of three parts, in the first part have been made the methodological strategies of the application of the lesson learning, in the second part, we present the scientific argument using citations of support and in the third part the psych pedagogical support that current education is based. _x000D_ Keywords: Education,